BS ISO 21219-21. Intelligent transport systems. Traffic and travel information (TTI) via transport protocol experts group, generation 2 (TPEG2). Part 21. Geographic location referencing (TPEG-GLR) (21st June 2023) - British Standards Institution,
No abstract available